An experimental investigation into mineral transformation, particle agglomeration and ash deposition during combustion of Zhundong lignite in a laboratory-scale circulating fluidized bed. (1st May 2019) - Liu, Zhuo; Li, Jianbo; Wang, Quanhai; Lu, Xiaofeng; Zhang, Yuanyuan; Zhu, Mingming; Zhang, Zhezi; Zhang, Dongke
Highlights: Bed agglomeration and ash deposition during CFB combustion investigated. Bottom ash was agglomerated due to the abundance of Fe and Na. Deposit showed a layered structure and was sintered by micron-sized Ca, S and Na. Fly ash was composed of Ca-, and S-rich clusters and micron Ca/Si/Al particulates. The transformation of Ca, Na, and Fe, and their role in ash deposition analysed. Abstract: The characteristics and mechanisms of inorganics and mineral transformation, particle agglomeration and ash deposition during Zhundong lignite combustion in a 0.2 t/d lab-scale circulating fluidized bed (CFB) furnace were experimentally investigated. A sample of Zhundong lignite with particle size <3 mm was combusted in the CFB operating at 950 °C. An ash deposition probe installed at the upper outlet of the cyclone maintained at 550 °C was used to simulate ash deposition. The bottom ash, ash deposit on the probe, and fly ash were collected and analysed using SEM-EDX, XRD, ICP-OES and an ash fusion analyser. It was found that the bottom ash was composed of discrete particles of SiO2, Fe2 O3, and NaAlSiO4 and etc., among which particles rich in Fe and Na had agglomerated. The deposit on the upwind surface of the probe showed a layered structure: a sintered cone-shape inner-layer rich in micron-sized Ca- and Na-bearing minerals, and a loose coarse-grained outer-layer dominated by silicates and aluminosilicates. The inner-layer was believed to have initiated the ash deposition while the outer-layer was believed to have been captured by the initiating layer. XRD analysis confirmed the presence of Ca- and Na-bearing minerals including CaSO4, NaAlSiO4, Na2 SO4 and Na2 Si2 O5 of low melting-points in the deposit. The fly ash was composed of ash particles or clusters enriched in CaSO4 and Ca2 Al2 SiO7 . Furthermore, ICP analysis revealed that Na was enriched in the deposit, while Fe was enriched in the bottom ash, both of which however were comparably less in the fly ash. Consequently, the fusion temperatures of the bottom ash and deposit were lower than that of the fly ash. In addition, mineral interactions between bed materials and Zhundong lignite ashes including Na capture by aluminosilicate were identified, affecting the partitioning of alkali and alkali earth during combustion and ash deposition in CFB.